Implementasi Program Pemberian Makan Tambahan Untuk Pencegahan Stunting Di Desa Talaga Warna - Rahmawati, Amelia Dwi; Lala, Elvina Novalianti; Sari, Indah Nurmala; Mulhadi, Muhamad; Dheanty, Nayla (UNIVERSITAS PGRI TULUNGAGUNG, 2024)
Stunting is a global issue of concern today so the government intensified Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction. The stunting rate in Serang Regency fluctuated from 2021 to 2023. Directorate General of Regional Development shows that Talaga Warna in 2021 has a stunting prevalence of 3.6%, in 2022 it has a stunting prevalence of 5.2% and a stunting prevalence of 7.1% in 2023. The purpose of this study was to determine how the implementation of the Supplementary Feeding Program for stunting prevention in Talaga Warna Village. The research method used is descriptive qualitative through document analysis and interviews with the theory of the Van Metter Van Horn. The results showed that the characteristics of implementing agents, inter-organizational communication, and existing resources were important factors in the successful implementation of the Supplementary Feeding Program. The success of the program is influenced by an understanding of policy objectives, effective coordination, and the ability to face social, economic, and political challenges. The implementation of the Supplementary Feeding Program provides good results so that the stunting rate in Talaga Warna Village decreases.